Implementation of EdTech SB-TraFo App 5.0 for Bullying Prevention and Student Character Strengthening at SMAN 6 Bengkulu Tengah - Hananda Fitra Pranatha; Yusran Panca Putra; Andes Permadi; Bogy Restu Ilahi; Muhammad Nuryogatama; Abdul Jamal (Asosiasi Profesi Multimedia Indonesia, 2026)
Background: Bullying is a significant issue in Indonesian schools, including SMAN 6 Bengkulu Tengah, with 32 recorded cases in 2024. This indicates a weakness in character education and the limited use of technology to address the problem. The student body's composition, with a majority of male students and parents working long hours, exacerbates the issue.Aims: This community service program aims to enhance anti-bullying awareness and strengthen students’ character through the Stepwise Behavioral Transformation (SB-TraFo) App. The program seeks to provide a proactive and transformative solution using educational technology (EdTech) to support the gradual behavioral transformation of students.Methods: The program consisted of five stages: (1) preparation and socialization, (2) character strengthening and anti-bullying classes, (3) SB-TraFo App training, (4) digital character literacy workshops for teachers and parents, and (5) establishment of the School Character Care Team (TSPK) for sustainability. A participatory and transformative approach actively engaged students, teachers, and parents.Results: The outcomes demonstrated significant improvements: students’ understanding of core character values increased by 84%, participation in digital reflection activities reached 82%, and bullying cases decreased by 37% within three months. Additionally, 90% of teachers and parents gained competence in digital character literacy, and over 80% of students used the SB-TraFo App consistently.Conclusion: The program successfully created a more empathetic, collaborative, and safe school environment. The integration of behavior-reflective EdTech proved effective in supporting sustainable character education and fostering synergy between technology, education, and human values in developing resilient young generations for the digital era